INNOVATION AND CREATIVITY IN TEACHING SPEAKING - Alistair Wood (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
The paper will examine the related ideas of innovation and creativity as applied to the teaching of speaking.  It will describe how the teaching of speaking can move beyond standard ways of presenting and practicing the skill, whether at secondary or tertiary level.   Creativity as presented means both on the part of the teacher and the part of students, since it demands that both teacher and students step out of their traditional roles and rethink what it means to speak in the classroom.  Different types of speaking will be looked at, from conversation to oral presentations, as well as various ways of integrating teaching and the other language skills.  Speaking will be related to more general ideas of problem solving and project work and other ways of harnessing creative ideas, as well as innovative ways of bringing in use of computers and online media to help in making speaking meaningful